Strengthening antimicrobial resistance diagnostics in National Reference Laboratories across One Health in South and Southeast Asia: impact of external quality assessment and targeted follow-up - Abegaz, Freshwork; Al-mir, Hiba; Kostyanev, Tomislav; Prifti, Kristi; Kwon, Soo-Young; Guarnacci, Tobin; Rasmussen, Lone Brink; Sujan, Mohammad Julhas; Teixeira Dos Santos, Patrícia; Prathan, Rangsiya; Luangtongkum, Taradon; Chanchaitong, Pattrarat; et al. (The journal of antimicrobial chemotherapy, 2025)
The intent of this study was to evaluate and improve microbiology laboratory diagnostic capacity in selected National AMR Reference laboratories from South and Southeast Asia for AMR testing utilizing EQA and targeted follow-up support.A baseline assessment was conducted to evaluate quality management system (QMS) practices for laboratories participating in the Strengthening External Quality Assessment in Asia (EQASIA-EQA) programme for the first time. Following each EQA iteration, laboratory assessments were conducted, and underperforming laboratories received online consultations to identify root causes of deviations and implement corrective and preventive actions (CAPA). Laboratories with persistent underperformance, onsite visits and targeted training sessions were provided to support quality improvement.Significant gaps were identified in the QMS of the 24 laboratories surveyed, with 38% lacking a QMS and 42% not conducting internal audits. Many laboratories lacked standard operating procedures (SOPs) for key processes, CAPA and equipment maintenance. Training and competency assessments were insufficient, with 50% of laboratories not conducting competency assessments. Additionally, 46% did not perform root cause analysis for EQA deviations, and 42% lacked a structured quality control programme. Water purity testing and equipment maintenance were also inadequate. Of the four baseline-assessed laboratories, three underperformed twice, and one underperformed three times across EQA iterations. Key deficiencies included the absence of a QMS and SOPs, as well as inadequate staff training and internal quality control. After targeted follow-up support, improvements were observed in QMS implementation, SOP development, staff training and quality control.Participation in EQA, combined with targeted follow-up support, enhances laboratory quality and performance. These improvements ultimately contribute to the provision of reliable data that can guide policy actions to combat AMR.